Navigating the path to sustainability in G20: Nexus of industrialization, economic development, resource management and green innovations - Dai, Wanci; Zhao, Chen (Frontiers in Environmental Science, 2025)
BackgroundEnvironmental sustainability (ENS) is a pressing challenge for G20 economies, requiring a delicate balance between economic growth, resource management, and green innovations. While previous research has explored ENS determinants, limited attention has been given to the synergistic effects of financial management (FEM), industrialization (IDL), resource efficiency (REM), economic growth (ENG), human capital (HCI), and green innovations (GEN) within the G20 framework.ObjectiveThis study evaluates the short- and long-term impacts of these factors on ENS, offering empirical evidence to guide sustainability policies in G20 nations.MethodsUtilizing panel data (2000–2022), the study applies Cross-Sectional Autoregressive Distributed Lag (CS-ARDL) to capture dynamic relationships, while Augmented Mean Group (AMG) and Common Correlated Effects Mean Group (CCEMG) estimations ensure robustness.Key FindingsResults indicate that FEM (β = 0.3361, p < 0.05), ENG (β = 0.2213, p < 0.01), and HCI (β = 0.1026, p < 0.01) significantly enhance ENS, emphasizing the crucial role of financial stability, economic expansion, and human capital in driving sustainability. Conversely, IDL (β = −0.8879, p < 0.01) and REM (β = −0.1425, p < 0.05) negatively affect ENS, highlighting the environmental risks of rapid industrialization and inefficient resource utilization. Robustness analysis further reveals that GEN positively influences ENS (β = 0.1442, p < 0.01), reinforcing the need for sustained eco-innovation investments.Policy ImplicationsTo enhance sustainability, G20 policymakers should prioritize green financial frameworks, promote human capital development, and foster technological innovations. Strategies should also mitigate the environmental costs of industrialization and improve resource efficiency. Strengthening institutional frameworks and fostering global cooperation will be essential in achieving long-term ENS and aligning with Sustainable Development Goals (SDGs).